On Evolute Curves In Terms Of Inextensible Flows Of In E3 - Korpinar, Talat; Bas, Selcuk (Soc Paranaense Matematica, 2018)
In this paper, we study inextensible flows of evolute curve of curves in E-3. We research inextensible flows evolute curves of in the E-3.
Keywords: Inextensible flows; evolute curve